1989
DOI: 10.4315/0362-028x-52.3.158
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Levels of Nitrite and Nitrate on the Survival of Listeria monocytogenes During the Manufacture of Fermented Sausage

Abstract: The fate of L. monocytogenes during the fermentation of Finnish fermented sausage was examined. L. monocytogenes was able to survive during a 21 d fermentation of sausage with levels of nitrite and salt commonly used in the meat industry today (120 ppm NaNO2 and 3.0% NaCl). Initial numbers of Listeria (103 CFU/g and 105 CFU/g) decreased approximately 1 log 10 CFU/g during the manufacture. Increasing the levels of nitrite/nitrate to those used 30 years ago in meat products had a marked effect on the elimination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…Concomitantly, the rational application of LAB starter cultures in sausage fermentations is important to suppress undesirable microorganisms, to stabilize the raw sausage, and to ensure high product quality. However, the meat-borne pathogen Listeria monocytogenes can survive acidic conditions, low a w , and high sodium chloride and sodium nitrite concentrations during the fermentation and drying of meat (13,20,21). Therefore, interest in bacteriocin-producing starter cultures with listericidal capacities has increased (9).…”
Section: Discussionmentioning
confidence: 99%
“…Concomitantly, the rational application of LAB starter cultures in sausage fermentations is important to suppress undesirable microorganisms, to stabilize the raw sausage, and to ensure high product quality. However, the meat-borne pathogen Listeria monocytogenes can survive acidic conditions, low a w , and high sodium chloride and sodium nitrite concentrations during the fermentation and drying of meat (13,20,21). Therefore, interest in bacteriocin-producing starter cultures with listericidal capacities has increased (9).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogen is inhibited by various acids and antimicrobials (Farber and Peterkin, 1991;Ryser and Marth, 1991). Nitrite is expected to be effective only when combined with reduced pH, cold temperatures and sodium chloride in cured meats (Junttila et al, 1989). Available scientific publications have indicated that L. monocytogenes may be of higher heat resistance than other non-spore-forming pathogenic bacteria (Mackey and Bratchell, 1989;Boyle et al, 1990;Schoeni et aI., 1991).…”
Section: Pathogens Of Emerging Concernmentioning
confidence: 99%
“…Traditionally, processors have relied on the intrinsic properties of dry fermented sausages, including low pH values due to lactic acid production by starter cultures and decreases in water activity, salt, and other antimicrobials (i.e., nitrite and various spices), to suppress the growth of pathogenic microorganisms (23). However, when pathogens such as Salmonella and L. monocytogenes are initially present at high levels, these populations may be reduced during the fermentation and drying phases of production but may persist in the final product (1,11,16,17).…”
mentioning
confidence: 99%